Lactate‐induced activation of HCA2 improves survival in mice with sepsis. Issue 6 (5th April 2019) - Takakura, Ayumi; Zandi-Nejad, Kambiz
ABSTRACT: Sepsis is characterized by systemic inflammation that is caused by infection and by activation of proinflammatory pathways, resulting in mitochondrial and cellular dysfunction leading to multiorgan failure. Here, we show the following: 1 ) in peritoneal immune cells, particularly macrophages, from mice that have undergone cecal ligation and puncture (CLP), hydroxycarboxylic acid receptor 2 (HCA2) expression increased in parallel with proinflammatory cytokines; 2 ) post‐CLP survival rates of Hca2 −/− knockout mice ( n = 22) were lower than those of wild‐type (WT) mice ( n = 15) ( P < 0.011), which is suggestive of a protective role for HCA2 in sepsis; 3 ) WT mice subjected to CLP‐induced sepsis and treated with lactated Ringer's solution (LR, n = 13) survived longer than those treated with normal saline ( n = 14; P < 0.027); 4 ) LR treatment of CLP‐induced sepsis reduced proinflammatory cytokine expression in CD11b + F4/80 + macrophages and promoted M2‐like polarization; 5 ) HCA2 was expressed by kidney in the setting of sepsis, but not by normal kidneys; 6 ) LR administration attenuated sepsis‐associated acute kidney injury (AKI), partly restored expression of the key regulator of mitochondrial biogenesis, peroxisome proliferator‐activated receptor γ coactivator 1α ( P < 0.03), and reduced proinflammatory cytokine production (TNF‐α, P < 0.04; IL‐1β, P < 0.006; IL‐6, P < 0.03). Our data suggest that lactate‐induced activation of HCA2 during sepsis activates a negative feedback loop to attenuate the inflammatory response. The data further suggest that fluid resuscitation with LR may benefit patients with sepsis, particularly those with sepsis‐associated AKI treated with potentially lactate‐depleting renal replacement therapies.—Takakura, A., Zandi‐Nejad, K. Lactate‐induced activation of HCA2 improves survival in mice with sepsis. FASEB J. 33, 7625–7634 (2019). www.fasebj.org